The Origin and Growth of Geography as a discipline at South Africa Universities - Visser, Gustav (African Sun Media, 2016)
The publication provides the first comprehensive text that reflects on a century of the development of geography as an academic discipline at South African universities. The book showcases a broad and textured review of South Africa's geography departments, their staff members, their times, and the different Geographies they engaged in. The book lays the foundation from which more expansive individual departmental histories can be written in the future.